Avascular necrosis of femoral head secondary to trauma in dogs: A clinical, radiological and computed tomographic evaluation - Patwa, Ruchi; Bishnoi, P.; Palecha, Sakar; Bishnoi, A.K.; Chourasia, Richa (Indian Journal of Veterinary Surgery, 2025)
Fracture of hip joint is very common following automobile accident. Hip joint abnormalities can cause hind limb lameness and subsequent muscular atrophy, leading finally to the development of osteoarthritis. The present report describes three clinical cases in client owned dogs with avascular necrosis of femoral head. Clinical examination along with computed radiographic (CR) and computed tomographic (CT) evaluation was done in all three dogs. All the dogs were presented with a history of chronic trauma and lameness of the affected limb with limb adduction. CR and CT images revealed separation of the femoral head from the neck, subcortical sclerotic changes in the femoral head and acetabulum, osteonecrosis and osteophyte formation at the femoral head. Haematological and biochemical evaluations revealed increased alkaline phosphatase levels and altered Ca:P ratio. From this study it was concluded that trauma and femoral head fracture were the common factors that could cause vascular necrosis of the femoral head, which could be diagnosed by CR and CT imaging.